Comparison of the Stature and Lower Limb Segment Lengths between Santhals and Banglalees of Pirganj, Rangpur (Bangladesh Journal of Anatomy, 2014)
Context: The relationship between height and long bone differs according to race, age, sex and size of the body. Anthropometric studies of bones convey information regarding race, sex, age and stature of a person. This information is of immense interest to the anatomist in the academic field as well as medico legal work. Climates, heredity, nutritional status of population are reported to have an effect on stature and length of long bones. The study was aimed at to the anthropometric measurement of stature and length of different segments of lower limb of adult Santhal males of Pirganj upazilla, Rangpur to find out any racial characteristics of their own and compared with Bangalee adult males of the same area to find out any racial variations between these two groups of populations. Materials and Methods: Stature is the standing height of a person. The study was done on 60 adult male Santhals and 120 adult male Bangalees. Measurements stature and different lower limb segment length (upper leg segment length, lower leg segment length, leg segment length) was done. Results :It was seen from the result of the present study that though height and upper leg segment length was higher in Bangalees than the Santhals, the lower leg segment length and leg segment length was significantly higher in the Bangalee males than the Santhals. Conclusion: The present study shows that the lower leg segment length and leg segment length was significantly higher in the Bangalee males than Santhals due to nutritional deficiency. DOI: http://dx.doi.org/10.3329/bja.v11i2.20674 Bangladesh Journal of Anatomy, July 2013, Vol. 11 No. 2 pp 71-76